LEGAL CONSEQUENCES OF AGREEMENTS MADE BY DIRECTORS WHOSE TERM OF OFFICE HAS ENDED - Siti Nurul Intan Sari Dalimunthe (Jurnal Scientia, 2022)
The appointment of the Board of Directors for the first time is carried out by the Founder of the Company through the Deed of Establishment. Article 94 paragraph 3 of the Indonesian Company Law does not stipulate the terms of office of the Directors, it only states that the Directors are appointed for a certain period and they can be reappointed. In practice, the Board of Directors is first appointed through a Deed of Establishment for a period of 3 (three) or 5 (five) years. The term of office of the Company's Board of Directors that has expired cannot be automatically extended but must be reappointed. Since the expiration of their period, the former Directors of the Company are no longer entitled to act for and on behalf of the Company. However, in practice there are still many companies not aware of the terms of office of the Directors, so they are negligent in re-appointing members of the Board of Directors. The purpose of this study is to find out the provisions for reappointing members of the Board of Directors and the legal consequences of agreements made by the Board of Directors whose terms of office have ended. The type of research in this study is normative juridical with statutory and conceptual approaches. The results of the study show that the reappointments of former Directors whose term of office has expired can be carried out through a GMS or Circular Decision (decisions of shareholders that are binding outside the GMS), which are outlined in a Notary Deed and notified to the Ministry of Law and Human Rights of the Republic of Indonesia to be recorded in the Company Register to obtain approval. The agreement signed by the former Board of Directors on behalf of the company whose term of office has ended is invalid because it does not fulfill the subjective element as required for a valid agreement (Article 1320 of the Indonesian Civil Code) which results in the agreement being canceled by one of the parties. If not canceled by one of the parties, then the agreement is personally binding on the Directors, not the company. Therefore, before the term of office of the Board of Directors ends, it is better for the company to re-appoint it through the GMS or Circular Decision and ratification to the Indonesian Ministry of Law and Human Rights so that the agreement is made by the Directors on behalf of the company can bind the company.